2017
DOI: 10.1080/09638288.2017.1300691
|View full text |Cite
|
Sign up to set email alerts
|

Modeling quality of life in patients with rheumatic diseases: the role of pain catastrophizing, fear-avoidance beliefs, physical disability, and depression

Abstract: The current results underscore the significant role of cognitive, affective, and behavioral factors in perceived physical disability and their mediated detrimental effect on physical and psychological quality of life in patients with rheumatic diseases. Implications for rehabilitation The fear-avoidance model is applicable to the prediction of quality of life in patients with rheumatic diseases. As pain-catastrophizing and fear-avoidance beliefs are important factors linked to physical disability and depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 39 publications
7
24
1
Order By: Relevance
“…Fatigue and pain are the most common extraglandular symptoms, 35 and pain severity explained 14% of the variance in disability of daily activities in Korean patients with pSS. 36 Our results were in line with previous studies reporting that pain is a major symptomatic problem related to low physical functioning and health outcomes. Therefore, systematic monitoring of pain treatment seems essential.…”
Section: Discussionsupporting
confidence: 93%
“…Fatigue and pain are the most common extraglandular symptoms, 35 and pain severity explained 14% of the variance in disability of daily activities in Korean patients with pSS. 36 Our results were in line with previous studies reporting that pain is a major symptomatic problem related to low physical functioning and health outcomes. Therefore, systematic monitoring of pain treatment seems essential.…”
Section: Discussionsupporting
confidence: 93%
“…They often avoid activities which are assumed to provoke a real or potential injury/reinjury, developing in turn, further physical inactivity 9. This fear to carry out certain movements can cause a negative vicious cycle where people with CMP show greater levels of pain, disability and emotional distress,9 and as a result, poor quality of life 101. Our results support this statement as we identified moderate and strong evidence of associations between a greater degree of kinesiophobia and greater levels of pain, greater levels of disability and poorer quality of life and in addition, moderate evidence that a greater degree of kinesiophobia is a predictor of the progression of disability overtime.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication on feline personality, it was also suggested that cats scoring low on agreeableness could be suffering from underlying pain 40 . The association between chronic pain and mood or depression has long been known in human medicine 41–43 …”
Section: Discussionmentioning
confidence: 99%